Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/app11041657
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electronic, and Optical Properties of Group 6 Doped Anatase TiO2: A Theoretical Approach

Abstract: Titania (TiO2) is a key material used as an electron transport in dye-sensitized and halide perovskite solar cells due to its intrinsic n-type conductivity, visible transparency, low-toxicity, and abundance. Moreover, it exhibits pronounced photocatalytic properties in the ultra-violet part of the solar spectrum. However, its wide bandgap (around 3.2 eV) reduces its photocatalytic activity in the visible wavelengths’ region and electron transport ability. One of the most efficient strategies to simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…67 which is in good agreement with the experimental value of 4.5[47] and other calculation works[48,49]. For RuTi 15 O 32 system, ( ) 0 1 e w = decreases in both x and z direction to about 2.89.…”
supporting
confidence: 89%
“…67 which is in good agreement with the experimental value of 4.5[47] and other calculation works[48,49]. For RuTi 15 O 32 system, ( ) 0 1 e w = decreases in both x and z direction to about 2.89.…”
supporting
confidence: 89%
“…We use SGGA + U and choose 10 × 10 × 5 k-point meshes in the geometry optimizations. We set U = 3 eV cause previous studies have shown that is sufficient for transition metal-doped anatase [44][45][46]. The force is less than 0.02 e V/Å −1 on each atom, and the calculation will be terminated till the energy is less than 10 -5 eV.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…Experimental results show that atom replacement doping is an effective way to generate magnetic properties and adjust the band gap [14,15]. Doping is applied to reduce the band gap of anatase as a strategy that can modulate the band gap effectively [16,17]. In the work of Aguilera del Toro et al [18], they succeeded in reducing the band gap by replacing the metal or non-metal in (TiO 2 ) 10 to control the impurity content.…”
Section: Introductionmentioning
confidence: 99%